Rožnice (Rosaceae) v Botaničnem vrtu Univerze v Mariboru in cianogeni glikozidi (University of Maribor Press, 2022)
Rosaceae in the Botanical Garden of the University of Maribor and Cyanogenic Glycosides. The monograph was prepared within the ŠIPK project entitled "Cyanogenic glycosides of rose family plants from the former castle garden area". The monograph introduces the reader to the Botanical Garden of the University of Maribor, describes the history of the garden and its connection with the Rosale. It gives the reader a brief introduction to the different parts of the garden, the rose garden, the morphology of roses, their history and taxonomy, events related to roses and the list of roses. Some edible rose plant species (apples, pears, raspberries, strawberries) and less edible ones (quince, pomegranate, service tree, blackberries, chokeberry, shadebush, medlar, the common lady’s mantle, heart power, hawthorn) are presented. Since many plants from the rosaceous family are used in daily nutrition, the material also includes a collection of recipes, introduces the harmful cyanogenic glycosides and shows methods by which we can determine their content in food. The book concludes with worksheets for children, students, and other garden visitors to learn more about roses and explore cyanogenic glycosides.